2021
DOI: 10.1002/cre2.440
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lip‐seal strength and its relation to oral motor functions

Abstract: Objectives: Lip-seal strength, which represents the muscle strength of the lips, appears to chiefly contribute to mastication and pronunciation. However, the functional characteristics of lip-seal strength in adults are still undefined. The present study aimed to understand not only the distribution of lip-seal strength in adult men and women but also the effect of age on this strength and identify oral motor functions correlated with lip-seal strength. Materials and methods:The subjects included 339 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In addition, statistically significant differences were observed in the labial seal (Table 1). This difference in the strength of the lip muscles was previously reported, which was confirmed in the present study (Miyamoto et al 2019;Kugimiya et al 2021b). In addition, tongue pressure and masticatory performance of oral motor function exhibited a significant correlation with lip sealing strength in both sexes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, statistically significant differences were observed in the labial seal (Table 1). This difference in the strength of the lip muscles was previously reported, which was confirmed in the present study (Miyamoto et al 2019;Kugimiya et al 2021b). In addition, tongue pressure and masticatory performance of oral motor function exhibited a significant correlation with lip sealing strength in both sexes.…”
Section: Discussionsupporting
confidence: 93%
“…2019; Kugimiya et al . 2021b). In addition, tongue pressure and masticatory performance of oral motor function exhibited a significant correlation with lip sealing strength in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some effects in the oral environment have few subjective symptoms, and periodic measurement may lead to early prevention for chronic diseases. While Kugimiya et al reported that lip seal strength has the effect by aging and was not normally distributed in adults, lip seal strength and tongue pressure were signi cantly correlated among adults in Japan [7] .…”
Section: Introductionmentioning
confidence: 90%
“…Before the study began, written consent for publication was obtained from all participants. Alcohol consumption, smoking, and overweight/obesity have been reported to be associated with nonrestorative sleep among healthy Japanese [7], so we administered a self-administered questionnaire composed of items on age, alcohol consumption (once a week or more, less than once a week), smoking (yes, no), weight (kg), height (cm), and obstructive sleep apnea (yes, no). Due to the COVID-19 pandemic in Japan, job descriptions are uid, such as changing from driver to clerk, so job descriptions were not included in the questionnaire.…”
Section: Study Participantsmentioning
confidence: 99%
“…However, from previous studies it remains unclear whether the difference in performance between SMR and AMR tasks is already evident in younger age groups or whether it follows an evolutionary pattern from childhood to adulthood, as has been reported for the syllabic rates of SMR and AMR tasks separately. Changes in performance between AMR and SMR from childhood to adulthood can hardly be inferred from previous studies since SMR and AMR tasks are not systematically tested in DDK studies (e.g., in children and adolescents [ 25 , 26 , 27 ], in adults [ 28 , 29 , 30 ] or whenever they are included, no comments on the performance pattern between the two types of DDK tasks is found (e.g., in children and adolescents [ 7 , 31 ] or in adults [ 13 , 14 ]). Additionally, most studies are carried out only on one age group or only on one type of DDK—mostly AMR—which does not inform of the changes in performance between AMR and SMR from childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%